Accuracy of a Cancer Registry Versus Clinical Care Team Chart Abstraction in Identifying Cancer Recurrence - Elsa A. Sutton, MD; Benjamin C. Kamdem Talom, BA; Daniel K. Ebner, MD, MPH; Taylor M. Weiskittel, MS; William G. Breen, MD; Roman O. Kowalchuk, MD; Heather J. Gunn, PhD; Courtney N. Day, MS; Eric J. Moore, MD; Sara J. Holton, CTR, BS Health/Health Care Administration/Management; Kathryn M. Van Abel, MD; Chadi N. Abdel-Halim, MD; et al. (Mayo Clinic Proceedings: Innovations, Quality & Outcomes, 2024)
Objective: To evaluate the completeness and reliability of recurrence data from an institutional cancer registry for patients with head and neck cancer. Patients and Methods: Recurrence information was collected by radiation oncology and otolaryngology researchers. This was compared with the institutional cancer registry for continuous patients treated with radiation therapy for head and neck cancer at a tertiary cancer center. The sensitivity and specificity of institutional cancer registry data was calculated using manual review as the gold standard. False negative recurrences were compared to true positive recurrences to assess for differences in patient characteristics. Results: A total of 1338 patients who were treated from January 1, 2010, through December 31, 2017, were included in a cancer registry and underwent review. Of them, 375 (30%) had confirmed cancer recurrences, 45 (3%) had concern for recurrence without radiologic or pathologic confirmation, and 31 (2%) had persistent disease. Most confirmed recurrences were distant (37%) or distant plus locoregional (29%), whereas few were local (11%), regional (9%), or locoregional (14%) alone. The cancer registry accuracy was 89.4%, sensitivity 61%, and specificity 99%. Time to recurrence was associated with registry accuracy. True positives had recurrences at a median of 414 days vs 1007 days for false negatives. Conclusion: Currently, institutional cancer registry recurrence data lacks the required accuracy for implementation into studies without manual confirmation. Longer follow-up of cancer status will likely improve sensitivity. No identified differences in patients accounted for differences in sensitivity. New, ideally automated, data abstraction tools are needed to improve detection of cancer recurrences and minimize manual chart review.